2020
DOI: 10.1186/s12876-020-01504-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and its associated factors among prisoners in a Nigerian prison

Abstract: Background The prison population is considered at high risk of acquiring infectious diseases due to confined conditions, behavioral factors, injection drug use, unprotected sexual activity, non-professional tattooing and scarification, and needle sharing. Hepatitis C virus (HCV) is a blood borne pathogen mostly transmitted via percutaneous exposure that results in inflammation of the liver. It is one of the public health problem worldwide and is the principal cause of parenterally transmitted non-A, non-B hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 40 publications
3
23
3
Order By: Relevance
“…There were however no reports of treatment discontinuation following this observed adverse events. In our study, there were more males 79 (52.7%) than females 71 (47.3%) and this same pattern of a higher male population has been reported by other Nigerian investigators [25][26][27]. We also observed that a majority of our study population were young to middle-aged patients and this may reflect the tendency for "at risk" behaviors commoner to these population.…”
Section: Safety Outcomessupporting
confidence: 90%
“…There were however no reports of treatment discontinuation following this observed adverse events. In our study, there were more males 79 (52.7%) than females 71 (47.3%) and this same pattern of a higher male population has been reported by other Nigerian investigators [25][26][27]. We also observed that a majority of our study population were young to middle-aged patients and this may reflect the tendency for "at risk" behaviors commoner to these population.…”
Section: Safety Outcomessupporting
confidence: 90%
“…In one systematic review of 23 articles, shared contaminated needles for IV drug use was reported as one of the principal hepatitis transmission routes among prisoners 59 . In another study carried out in Nigeria, 29.6% of inmates who used injection drugs were HCV positive 39 . Similarly, one large study among 1336 inmates in Ghana, indicated intravenous drug use, history of sharing syringes and drug paraphernalia, as independent determinants for HIV, HBV, and syphilis 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Prisoners with no history of institutional education (illiterate) were mentioned by nine articles, and the rate of complete illiteracy among participants ranged from 1.5% to 30.9%. 3 , 14 , 16 , 18 , 24 , 25 , 27 , 39 , 43 In addition, eight articles reported that their sample participants had only completed high school education, with a percentage ranging from 9.32% to 60%. 3 , 15 , 16 , 19 , 24 , 26 , 31 , 34 , 44 Finally, only eight studies reported higher educational levels among their participants, and reported university/college education from a low of 2.5% to a peak of 16.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-2 infection is known to recruit at the site of replication white blood cells including B and CD8 lymphocyte that can be infected by KSHV. In addition, reactivation of HSV-2 might increase the load at mucosal and systemic levels of other viruses including KSHV, HIV [26] , and HCV [27] . Viral shedding and transmission to sex partners can occur in the absence of symptoms or a noticeable lesion [28] .…”
Section: Discussionmentioning
confidence: 99%